The economic effects of the EU biofuel target - Bettina Kretschmer; Daiju Narita; Sonja Peterson (Energy Economics, 2009)
In this paper we use the CGE model DART to assess the economic impacts and optimality of different aspects of the EU climate package. A special focus is placed on the 10% biofuel target in the EU. In particular we analyze the development in the biofuel sectors, the effects on agricultural production and prices, and finally overall welfare implications. One of the main findings is that the EU emission targets alone lead to onlyminor increases in biofuel production. Additional subsidies are necessary to reach the 10% biofuel target. This in turn increases European agricultural prices by up to 7%. Compared to a cost-effective scenario in which the EU 20% emission reduction target is reached, additional welfare losses occur due to separated carbon markets and the renewable quotas. The biofuel target has relatively small negative or even positive welfare effects in some scenarios.
Keywords: D58; Q48; Q54; 330; CGE model; Climate policy; EU; Biofuels